Different habitus but similar electrocardiogram: Cardiac repolarization parameters in children - Comparison of elite athletes to obese children - Christian Paech; Janina Moser; Ingo Dähnert; Franziska Wagner; Roman Antonin Gebauer; Toralf Kirsten; Mandy Vogel; Wieland Kiess; Antje Körner; Bernd Wolfarth; Jan Wüstenfeld (Wolters Kluwer Medknow Publications, 2019)
Introduction: The standard 12-lead electrocardiogram (ECG) remains a widely used tool in the basic cardiac evaluation of children and adolescents. With the emergence of inherited arrhythmia syndromes, the period of cardiac repolarization has been the focus of attention. So far, data on cardiac repolarization and its normal variants in healthy children are scarce. This may cause uncertainties in the differentiation between pathologies and normal variants. As abnormal autonomic regulation seems to be a major influencing factor on cardiac repolarization, this study aimed to evaluate the parameters of cardiac repolarization of children in extremely good physical shape to obese children to improve knowledge about cardiac repolarization in these subgroups of pediatric patients that are vastly affected by the alterations of autonomic regulation. Methods: A total of 426 pediatric volunteers (84 lean, healthy controls; 130 obese healthy pediatric volunteers; and 212 elite athletes) were enrolled in the study, and the parameters of cardiac repolarization were determined in 12-lead ECG. Results: Most importantly, there were no pathological findings, neither in the healthy controls nor in the obese or athletes. Athletes showed overall shorter corrected QT intervals than children from the other groups. This is also true if a correction of the QT interval is performed using the Hodges formula to avoid bias due to a tendency to lower heart rates in athletes. Athletes showed the shortest Tpeak-to-end ratios between the groups. The comparison of athletes from primarily strength and power sports versus those from endurance sports showed endurance-trained athletes to have significantly longer QT intervals. Conclusions: This study suggests that neither obesity nor extensive sports seems to result in pathological cardiac repolarization parameters in healthy children. Therefore, pathology has to be assumed if abnormal repolarization parameters are seen and might not be simply attributed to the child's habitus or an excellent level of fitness.